Utilization of agroindustrial residues for lipase production by solid-state fermentation - Damaso,Mônica Caramez Triches (2008)
The aim of this work was to produce lipases by solid-state fermentation (SSF) using, as substrate, agroindustrial residue supplemented with by-products from corn oil refining process or olive oil. For a group of ten fungi strains selected in the first steps, the lipase activity obtained by SSF varied from 7.7 to 58.6 U/g of dry substrate (gds). Among the evaluated strains, the Aspergillus niger mutant 11T53A14 was selected by presenting the best enzymatic production. For the fermentation tests, two substrates were also investigated: wheat bran and corn cob, both supplemented with olive oil. The best results were obtained with wheat bran. Additionally, three industrial by-products from corn oil refining (soapstock, stearin and fatty acids) were evaluated as substitutes to the olive oil in the function of lipases production inducer. Among them, soapstock and stearin were the best inducers, whereas fatty acids presented an inhibitor effect. The highest lipase activities using soapstock, stearin and fatty acids were 62.7 U/gds, 37.7 U/gds and 4.1 U/gds, respectively.